The chloroplast genome sequence of an aquatic plant, Sparganium eurycarpum subsp. coreanum (Typhaceae). Issue 1 (2nd January 2019) - Gil, Hee-Young; Ha, Young-Ho; Choi, Kyoung Su; Lee, Jung Sim; Chang, Kae Sun; Choi, Kyung
Abstract: The complete chloroplast genome sequence of Sparganium eurycarpum subsp. coreanum was determined. The genome size was 161, 761 bp in length with 36.9% GC content. It included a pair of inverted repeats (IRa and IRb) of 26, 886 bp, which were separated by small single copy (SSC: 19, 029 bp) and large single copy (LSC: 88, 960 bp) regions. The cp genome contained 112 genes, including 79 protein-coding genes, 29 tRNA genes, and 4 rRNA genes. Phylogenetic analysis of the combined 79 protein-coding genes showed that S. eurycarpum subsp. coreanum was most closely related to Typha latifolia .